2013
DOI: 10.1371/journal.pone.0054405
|View full text |Cite
|
Sign up to set email alerts
|

Using Gross Energy Improves Metabolizable Energy Predictive Equations for Pet Foods Whereas Undigested Protein and Fiber Content Predict Stool Quality

Abstract: Because animal studies are labor intensive, predictive equations are used extensively for calculating metabolizable energy (ME) concentrations of dog and cat pet foods. The objective of this retrospective review of digestibility studies, which were conducted over a 7-year period and based upon Association of American Feed Control Officials (AAFCO) feeding protocols, was to compare the accuracy and precision of equations developed from these animal feeding studies to commonly used predictive equations. Feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 13 publications
2
71
1
1
Order By: Relevance
“…Although protein adequacy requires the correct amino acids to be absorbed in their appropriate concentrations, the total tract protein digestibility is a valuable indicator of protein nutrition. The recommended minimum concentrations have been shown to be more than adequate with normal pet food ingredients in the dog [3] and the cat [4] in foods with protein digestibility similar to the averages reported by Hall et al [5].…”
Section: Introductionsupporting
confidence: 78%
“…Although protein adequacy requires the correct amino acids to be absorbed in their appropriate concentrations, the total tract protein digestibility is a valuable indicator of protein nutrition. The recommended minimum concentrations have been shown to be more than adequate with normal pet food ingredients in the dog [3] and the cat [4] in foods with protein digestibility similar to the averages reported by Hall et al [5].…”
Section: Introductionsupporting
confidence: 78%
“…Kendall et al (1982) reported mean values (n = 106) of 83, 84, and 77% for wet, intermediate, and dry commercial canine foods. Hall et al (2013) reported standardized total tract protein digestibility coefficients for 331 dry and moist canine foods of 89.7 and 88.0%, respectively. Expression to apparent digestibility values yields estimates that are approximately 6 percentage units lower.…”
Section: Discussionmentioning
confidence: 99%
“…Expression to apparent digestibility values yields estimates that are approximately 6 percentage units lower. Although the apparent digestibility values reported by Hall et al (2013) are approximately 83%, two-thirds of the foods were not commercially available and premium foods were overrepresented (D. E. Jewell, Hill's Pet Nutrition, Topeka, Kansas, personal communication). Although a value of 70% appears to be low, Hervera (2011) reported an aFD N value in commercial dog foods of 71%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being carnivores, dietary fibers and undigested proteins are important for maintaining gastrointestinal health and stool quality in cats. Dietary fiber promotes laxation and short‐chain fatty acid production as in other species [Hall et al, ; Kerr et al, ]. Feline hindgut microbiota are highly active and are capable of fermenting plant‐ and animal‐based substrates [Sunvold et al, ; Depauw et al, ], resulting in increased fecal short‐chain fatty acid concentrations and reduced fecal pH [Kerr et al, ].…”
Section: Discussionmentioning
confidence: 99%